2019
DOI: 10.3390/app9050916
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Fluorescence Index Derived from the Slope Characteristics of Laser-Induced Chlorophyll Fluorescence Spectrum for Rice Leaf Nitrogen Concentration Estimation

Abstract: Leaf nitrogen concentration (LNC) is a major biochemical parameter for estimating photosynthetic efficiency and crop yields. Laser-induced fluorescence, which is a promising potential technology, has been widely used to estimate the growth status of crops with the help of multivariate analysis. In this study, a fluorescence index was proposed based on the slope characteristics of fluorescence spectrum and was used to estimate LNC. Then, the performance of different fluorescence characteristics (proposed fluore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…LIF was also successfully applied to study the effects of dimethoate on physiological and growth responses of pigeon pea plants and to measure out its application (Pandey et al, 2015 ). A fluorescent index was also proposed to estimate leaf nitrogen concentration in rice (Yang et al, 2019 ). In particular, differently to reflectance measurements (see sections 2.2 and 2.5), the signal is not affected by soil properties; so, ChlF sensors can be applied to estimate Chl content (linked to nitrogen availability) even in the early crop stages (after plant emergence or transplant) or in sparse soil coverage conditions (Casa et al, 2016 ).…”
Section: Remote Sensing Qualitative Methods For Stress Assessmentmentioning
confidence: 99%
“…LIF was also successfully applied to study the effects of dimethoate on physiological and growth responses of pigeon pea plants and to measure out its application (Pandey et al, 2015 ). A fluorescent index was also proposed to estimate leaf nitrogen concentration in rice (Yang et al, 2019 ). In particular, differently to reflectance measurements (see sections 2.2 and 2.5), the signal is not affected by soil properties; so, ChlF sensors can be applied to estimate Chl content (linked to nitrogen availability) even in the early crop stages (after plant emergence or transplant) or in sparse soil coverage conditions (Casa et al, 2016 ).…”
Section: Remote Sensing Qualitative Methods For Stress Assessmentmentioning
confidence: 99%
“…In this study, a three-layer neural network was selected to analyse the LNC based on the built inverse model. According to previous research [11], the 'trainbr' was used to serve as the training function. In addition, the size of hidden layer was set as four in this model.…”
Section: Methodsmentioning
confidence: 99%
“…Based on the passive hyperspectral remote sensing technology, studies have been conducted by some scholars to build different models to obtain more accurate biochemical parameter estimation. They proposed different vegetation indices based on statistical analysis models for estimating biochemical parameters or crops yields [10][11][12][13]. However, passive hyperspectral technology is difficult to acquire the spatial information.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Kuruvilla and Gunavathi [29] classified cancer using ANN-BP and obtained information that traingdx provided higher performance than traingda and traingdm functions. Then, Yang et al [30] studied leaf nitrogen concentration (LNC) estimates with trials of activation functions "trainrp," "trainbr," and "trainlm". The results demonstrated that trainrp provided optimal results and was more accurate than trainbr and trainlm.…”
Section: Introductionmentioning
confidence: 99%